Tungsten carbide-based nanocrystalline hard alloy and preparation method thereof
By introducing lanthanide metals, high-entropy metal carbides or high-entropy metal carbon nitride powder and boron carbide into nanocrystalline cemented carbide, and introducing cobalt and lanthanide metal elements through immersion and calcination, the complex problems of the existing nanocrystalline cemented carbide preparation process are solved, and higher hardness, toughness and high temperature resistance are achieved.
Patent Information
- Application Number
- CN202510164557.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-14
AI Technical Summary
The preparation process of existing nanocrystalline cemented carbides is relatively complex and it is difficult to meet the performance requirements of certain special occasions.
Tungsten carbide-based nanocrystal carbide is used to combine the lanthanide metal, high entropy metal carbide or high entropy metal carbon nitride powder and boron carbide, and cobalt and lanthanide metal elements are introduced through soaking and calcining to prepare tungsten carbide-based nanocrystal carbide.
It effectively inhibits the growth of tungsten carbide grains, improves the hardness, toughness and high temperature resistance of cemented carbide, and simplifies the preparation process.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanocrystalline cemented carbide, and in particular to tungsten carbide-based nanocrystalline cemented carbide and a preparation method thereof. Background Art
[0002] Cemented carbide is widely used in the manufacture of cutting tools such as turning tools, milling cutters, drill bits, wire drawing dies, bolt dies, nut dies, rock drilling tools, mining tools, drilling tools, etc. A system of cemented carbide materials is mainly a composite material composed of high-hardness tungsten carbide and metal cobalt bonding phase, in which tungsten carbide provides hardness for the alloy material and cobalt provides toughness for the alloy material, making the alloy material have excellent hardness, wear resistance, toughness, high temperature resistance and corrosion resistance.
[0003] The size of tungsten carbide grains in cemented carbide materials will directly affect the performance of the material. As the size of tungsten carbide grains decreases, the hardness and bending strength of cemented carbide materials continue to increase. In the technical field of this application, tungsten carbide with an average grain size of 0.6 to 0.8 μm is generally defined as sub-micron crystal cemented carbide, tungsten carbide with an average grain size of 0.2 to 0.6 μm is defined as ultra-fine crystal cemented carbide, and tungsten carbide with an average grain size of less than 0.2 μm is defined as nano-grained cemented carbide. Nano-crystalline cemented carbide has significantly higher hardness, wear resistance, red hardness, bending strength and impact toughness than ultra-fine crystal cemented carbide.
[0004] In order to inhibit the growth of tungsten carbide grains, it is usually necessary to use a grain growth inhibitor. For example, in the ultrafine-grained cemented carbide and its preparation method disclosed in Chinese invention patent CN117684036B and the ultrafine-grained cemented carbide and its preparation method disclosed in CN111378886B, conventional carbides such as VC and Cr3C2 are used as grain growth inhibitors to keep the particle size of tungsten carbide at the ultrafine grain level. However, with the continuous development of the manufacturing industry, the requirements for the performance of cemented carbide tools are constantly increasing. The performance of ultrafine-grained cemented carbide is difficult to meet the requirements of certain special occasions, which requires the development and preparation of nanocrystalline cemented carbide to further improve the performance and service life of cemented carbide.
[0005] The applicant of the present application has found through experiments that conventional carbides such as VC and Cr3C2 as grain growth inhibitors have poor grain growth inhibition effect on tungsten carbide with an average grain size of less than 0.2μm, resulting in the existing preparation process of nanocrystalline cemented carbide being more complicated. Therefore, it is necessary to develop a new preparation process for nanocrystalline cemented carbide. Summary of the invention
[0006] In order to solve the technical problem that the preparation process of nanocrystalline cemented carbide in the prior art is relatively complicated, the present invention provides tungsten carbide-based nanocrystalline cemented carbide and a preparation method thereof, and the technical solution is as follows: The preparation method of tungsten carbide-based nanocrystalline cemented carbide comprises the following steps: The tungsten carbide powder is immersed in a modified solution containing a soluble cobalt salt and a soluble lanthanide metal salt, and after the immersion is completed, a solid is collected, washed and dried to obtain a first powder; calcining the first powder under a reducing atmosphere to obtain a second powder; The second powder, high entropy metal carbide powder or high entropy metal carbonitride powder and boron carbide powder are mixed, and then molded and sintered to obtain tungsten carbide-based nanocrystalline cemented carbide.
[0007] As a further improvement of the above-mentioned preparation method of tungsten carbide-based nanocrystalline cemented carbide: it also includes soaking the tungsten carbide in a hydrofluoric acid solution before impregnation, and collecting, washing and drying the tungsten carbide after the soaking is completed.
[0008] As a further improvement of the preparation method of the above-mentioned tungsten carbide-based nanocrystalline cemented carbide: the mass fraction of the hydrofluoric acid solution is 10-15%, the immersion solid-liquid ratio is 1g:(20-50mL), the immersion time is 0.5-1 hour, the immersion temperature is 40-50°C, washing to neutrality, and vacuum drying at 60-70°C.
[0009] As a further improvement of the preparation method of the above-mentioned tungsten carbide-based nanocrystalline cemented carbide: the lanthanide metal in the soluble lanthanide metal salt is at least one of lanthanum, cerium, praseodymium, dysprosium, neodymium, promethium, samarium, europium, and terbium; in the modified solution, the concentration of cobalt ions is 0.1-0.5 mol / L, and the concentration of lanthanide metal ions is 0.01-0.05 mol / L; equal volume immersion is adopted, the immersion time is 2-4 hours, the immersion temperature is 50-60°C, washing is carried out until neutral, and vacuum drying is carried out at 60-70°C.
[0010] As a further improvement to the preparation method of the above-mentioned tungsten carbide-based nanocrystalline cemented carbide: the soluble cobalt salt is cobalt nitrate; the soluble lanthanide metal salt at least includes dysprosium nitrate, and the molar fraction of dysprosium nitrate is 40-60% of the total molar amount of the soluble lanthanide metal salt.
[0011] As a further improvement of the above-mentioned preparation method of tungsten carbide-based nanocrystalline cemented carbide: the reducing atmosphere is a mixture of nitrogen and hydrogen, the volume fraction of hydrogen is 20-30% of the total volume of the reducing atmosphere, the calcination temperature is 700-900°C, and the calcination time is 4-8 hours.
[0012] As a further improvement to the preparation method of the above-mentioned tungsten carbide-based nanocrystalline cemented carbide: the weight ratio of the second powder, high entropy metal carbide powder or high entropy metal carbonitride powder, and boron carbide powder is 100:(0.2-1.5):(0.1-0.5); the metal placeholders in the high entropy metal carbide powder or high entropy metal carbonitride powder are composed of at least five of vanadium, chromium, titanium, zirconium, hafnium, niobium, tantalum, and molybdenum in an equiatomic ratio; the average particle size of the tungsten carbide powder, high entropy metal carbide powder or high entropy metal carbonitride powder, and boron carbide powder is 50-150nm.
[0013] As a further improvement to the above-mentioned method for preparing tungsten carbide-based nanocrystalline cemented carbide: the sintering temperature is 1500-1650°C.
[0014] As a further improvement of the preparation method of the above-mentioned tungsten carbide-based nanocrystalline cemented carbide: first sintering under vacuum for 4 to 6 hours, and then sintering under 100 to 200 MPa for 1 to 2 hours.
[0015] The tungsten carbide-based nanocrystalline hard alloy is prepared by the above-mentioned preparation method of the tungsten carbide-based nanocrystalline hard alloy.
[0016] The tungsten carbide-based nanocrystalline cemented carbide and the preparation method thereof of the present invention have the following advantages: First, the lanthanide metal introduced in the present invention has a strong deoxidizing property, and oxygen is an important factor promoting grain growth in the alloy, so the addition of lanthanide metal can indirectly inhibit the growth of grains by reducing the oxygen content. The compounds of lanthanide metals will form particles on the grain boundaries, which can fix the grain boundaries, enhance the strength of the grain boundaries, and prevent the free growth of grains under high temperature or long-term heat treatment. Lanthanide metals often form solid solutions in the matrix material, and the formation of solid solutions can increase the distortion of the lattice, making the grains more stable at high temperatures and inhibiting the growth of grains. Lanthanide metals can enhance the creep resistance of the alloy at high temperatures and inhibit the growth of grains caused by high-temperature creep. Lanthanide metals can also change the phase diagram of the alloy, so that a more stable phase or a refined structure appears in the alloy, especially in a high-temperature environment, to enhance phase stability and prevent excessive coarsening of grains.
[0017] High-entropy alloys are alloys formed by five or more equal or approximately equal amounts of metals. The definition of alloy is a substance with metallic properties synthesized by two or more metals and metals or non-metals. The present invention introduces high-entropy metal carbide powder or high-entropy metal carbonitride powder with high entropy and alloy properties as a grain growth inhibitor, which can form a stable grain boundary in the tungsten carbide matrix, inhibit the excessive growth of grains, further enhance the high-temperature strength and oxidation resistance of the alloy under extreme conditions, and enhance the wear resistance and toughness of the overall alloy. At the same time, high-entropy metal carbides or high-entropy metal carbonitrides are easy to form nanocrystalline structures, solid solutions and second-phase particles (such as metal compounds, metal oxides, carbides, etc.) during the preparation process, and can form a "pinning effect" under high temperature or high stress conditions, increase grain boundary density and strength, reduce grain migration, and reduce grain growth rate, thereby further limiting grain growth.
[0018] Boron carbide is a hard, chemically stable material with a melting point of up to 2450°C. It can remain stable at high temperatures and form a physical barrier during the sintering process, which increases the strength of the interface, strengthens the mutual restraint between grains, hinders the migration of grains in the matrix material, and reduces the diffusion rate, thereby effectively limiting the growth of grains. Boron carbide also has a strong antioxidant ability, so it can effectively prevent the oxidation of the matrix material in a high temperature environment, further avoid the growth of grains or changes in alloy composition caused by oxidation, and effectively improve the high temperature performance, hardness, strength and other performance indicators of the alloy material.
[0019] Second, compared with the conventional mixed powder solution of directly using cobalt powder and lanthanide metal oxide powder, the present invention introduces cobalt and lanthanide metal elements by impregnation and calcination, which has the following advantages: (1) Directly adding metal powder requires a lot of ball milling mixing time, which can easily lead to uneven distribution of cobalt and lanthanide metals, especially in the case of larger particle powders. The metal elements may only act on the surface or in local areas, making it difficult to achieve uniform distribution. The present invention introduces cobalt and lanthanide metal elements by immersion, which can be more evenly attached to the surface of tungsten carbide, which is crucial for forming a stable nanocrystalline structure and can improve the overall performance of cemented carbide.
[0020] (2) For physical addition, if the particle size of the metal powder is large, it is easy to cause insufficient interaction between particles or uneven sintering density during the sintering process, resulting in poor density and performance of the final alloy, and the smaller the particle size, the higher the cost. In the chemical reduction addition scheme using immersion + calcination in the present invention, the cobalt element and the lanthanide metal element are first contacted with the tungsten carbide particles through the solution as ions, and then reduced to metal or oxide in situ during the calcination process, which reduces the risk of agglomeration of the metal powder during the sintering process, thereby helping to improve the sintering density and ultimately improve the mechanical properties and thermal stability of the cemented carbide.
[0021] (3) Metal powder is easily oxidized in the air, and its activity will be greatly reduced after oxidation, affecting the performance of the final cemented carbide. The cobalt element and lanthanide metal element introduced by the present invention through the soaking + calcination method can directly form an alloy with the tungsten carbide powder during the calcination process without being disturbed by oxidation, effectively avoiding the oxidation problem of the metal powder.
[0022] (4) Physical addition and mixing may result in insufficient bonding between metal powder particles and tungsten carbide particles, especially when the metal powder particle size is large, the bonding surface is small, which may affect the strength and toughness of cemented carbide. The present invention directly reacts with the surface of tungsten carbide by solution immersion, which can more effectively form a metal-tungsten carbide interface. The calcination reduction process further ensures the uniform distribution and tight bonding of metal elements, enhances the bonding force between tungsten carbide particles and metal phases, and optimizes the overall structure of the alloy.
[0023] (5) Direct physical addition of metal powder may lead to agglomeration of larger particles, making it difficult to form fine nanocrystalline particles, which in turn affects the mechanical properties of cemented carbide, especially its stability at high temperatures. The soaking + calcining scheme of the present invention introduces metal elements through chemical reactions and promotes grain refinement through the calcination process, which can effectively inhibit the growth of grains and thus form a stable nanocrystalline structure, which is crucial for improving the hardness, wear resistance and high temperature strength of the alloy.
[0024] In summary, the present invention utilizes the combined effects of lanthanide metals, high entropy metal carbide powder or high entropy metal carbonitride powder and boron carbide and adopts a new introduction method, so that the particle size of tungsten carbide is effectively suppressed, and nanocrystalline cemented carbide with excellent hardness, toughness and high temperature resistance is successfully prepared, which effectively solves the technical problem of the relatively complicated preparation process of nanocrystalline cemented carbide in the prior art and has strong practicality.
[0025] The present invention is further described below by way of specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through practice of the present invention. DETAILED DESCRIPTION
[0026] The present invention is described clearly and completely below. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention, it should be noted that: The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0027] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0029] Embodiment 1: The preparation method of tungsten carbide-based nanocrystalline cemented carbide of this embodiment comprises the following steps: (1) Soak the tungsten carbide in a hydrofluoric acid solution with a mass fraction of 13%, with a solid-liquid ratio of 1g: (40mL), a soaking time of 1 hour, and a soaking temperature of 40°C. After soaking, collect the tungsten carbide, wash it to neutrality, and vacuum dry it at 70°C. Soaking in hydrofluoric acid can remove oxides and impurities on the surface of tungsten carbide powder, make the surface of tungsten carbide more active, and improve the adhesion and reactivity of the subsequent modified solution on the surface of tungsten carbide.
[0030] (2) Soaking the tungsten carbide powder in a modified solution containing a soluble cobalt salt and a soluble lanthanide metal salt, wherein the concentration of cobalt ions in the modified solution is 0.3 mol / L, and the concentration of lanthanide metal ions is 0.04 mol / L. The solution is soaked in equal volumes at a temperature of 60°C for 3 hours. After the soaking is completed, the solids are collected, washed to neutrality, and vacuum dried at 70°C to obtain a first powder.
[0031] Wherein, the soluble cobalt salt is cobalt nitrate; the soluble lanthanide metal salts are neodymium nitrate, samarium nitrate and dysprosium nitrate, and the molar fraction of dysprosium nitrate accounts for 40% of the total molar amount of the soluble lanthanide metal salts.
[0032] (3) The first powder is calcined in a reducing atmosphere at a temperature of 800° C. for 6 hours to obtain a second powder.
[0033] (4) The second powder, high entropy metal carbide powder or high entropy metal carbonitride powder, and boron carbide powder are weighed in a weight ratio of 100:1:0.3 to obtain a raw powder, and then a cemented carbide grinding ball with a diameter of 2 cm is added to a horizontal ball mill at a ball-to-material mass ratio of 7:1. The cemented carbide grinding ball, the raw powder, and a small amount of paraffin powder (2% of the mass of the raw powder) are added to the ball mill for 48 hours, and then the powder with a particle size of ≥140 mesh is screened and 2T / cm 2 The powder is pressed into a green body under pressure.
[0034] Then the green body was sintered at 1650°C with a heating rate of 10°C / min, firstly sintered under vacuum for 5 hours and then sintered under 150 MPa for 1 hour, to obtain tungsten carbide-based nanocrystalline cemented carbide.
[0035] Among them, the average particle size of tungsten carbide powder is 126nm, the average particle size of high entropy metal carbide powder or high entropy metal carbonitride powder is 105nm, and the average particle size of boron carbide powder is 97nm.
[0036] The metal placeholders in the high entropy metal carbide powder or high entropy metal carbonitride powder are composed of vanadium, chromium, titanium, zirconium, hafnium, niobium, tantalum and molybdenum in equal atomic proportions. The single substance powder or oxide powder of the placeholder metal is evenly mixed with carbon powder, and then the mixed powder is reacted at 1400° C. in a reducing atmosphere to obtain high entropy metal carbide powder or high entropy metal carbonitride powder.
[0037] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 132 nm, the high-temperature Rockwell hardness is 93.5 HRA, the transverse rupture strength is 4150 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.11%.
[0038] Example 2: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example has the following difference: the molar fraction of dysprosium nitrate accounts for 60% of the total molar amount of the soluble lanthanide metal salt.
[0039] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 134 nm, the high-temperature Rockwell hardness is 93.3 HRA, the transverse rupture strength is 4180 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.11%.
[0040] Example 3: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example is different in that the soluble lanthanide metal salt is neodymium nitrate, samarium nitrate and lanthanum nitrate.
[0041] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 141 nm, the high-temperature Rockwell hardness is 92.9 HRA, the transverse rupture strength is 4160 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.12%.
[0042] Example 4: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example is different in that the soluble lanthanide metal salt is neodymium nitrate and samarium nitrate.
[0043] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 148 nm, the high-temperature Rockwell hardness is 91.8 HRA, the transverse rupture strength is 4130 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.14%.
[0044] Example 5: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example is different in that the weight ratio of the second powder, high entropy metal carbide powder or high entropy metal carbonitride powder, and boron carbide powder is 100:0.2:0.1.
[0045] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 135 nm, the high-temperature Rockwell hardness is 93.1 HRA, the transverse rupture strength is 4200 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.12%.
[0046] Example 6: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example is different in that the weight ratio of the second powder, high entropy metal carbide powder or high entropy metal carbonitride powder, and boron carbide powder is 100:1.5:0.5.
[0047] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 131 nm, the high-temperature Rockwell hardness is 92.3 HRA, the transverse rupture strength is 4210 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.10%.
[0048] Comparative Example 1: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example has the following difference: the molar fraction of dysprosium nitrate is 35% of the total molar amount of the soluble lanthanide metal salt.
[0049] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 132 nm, the high-temperature Rockwell hardness is 92.3 HRA, the transverse rupture strength is 4140 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.12%.
[0050] Comparative Example 2: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example has the following difference: the molar fraction of dysprosium nitrate accounts for 65% of the total molar amount of the soluble lanthanide metal salt.
[0051] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 131 nm, the high-temperature Rockwell hardness is 94.2 HRA, the transverse rupture strength is 4040 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.13%.
[0052] Comparative Example 3: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example is different in that cobalt, neodymium oxide, samarium oxide and dysprosium oxide are directly physically added and mixed with tungsten carbide.
[0053] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 149 nm, the high-temperature Rockwell hardness is 91.6 HRA, the transverse rupture strength is 4100 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.15%.
[0054] Comparative Example 4: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example is different in that high entropy metal carbide powder or high entropy metal carbonitride powder is not used.
[0055] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 146 nm, the high-temperature Rockwell hardness is 92.1 HRA, the transverse rupture strength is 4050 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.15%.
[0056] Comparative Example 5: Compared with Example 1, the preparation method of tungsten carbide-based nanocrystalline cemented carbide in this example is different in that boron carbide powder is not applicable.
[0057] According to tests, the average particle size of the tungsten carbide-based nanocrystalline cemented carbide in this embodiment is 145 nm, the high-temperature Rockwell hardness is 91.8 HRA, the transverse rupture strength is 3980 MPa, and the weight gain after oxidation in an 800° C. air environment for 10 hours is 0.15%.
[0058] The embodiment of the tungsten carbide-based nanocrystalline cemented carbide of the present invention is prepared by the preparation method of the tungsten carbide-based nanocrystalline cemented carbide of any one of the above embodiments.
[0059] In the above-mentioned embodiments and comparative examples, the reducing atmosphere is a mixture of nitrogen and hydrogen, and the volume fraction of hydrogen is 20-30% of the total volume of the reducing atmosphere.
[0060] The average grain size of tungsten carbide-based nanocrystalline cemented carbide was tested using transmission electron microscopy.
[0061] High temperature Rockwell hardness is tested using the method specified in the Chinese national standard GB / T 230.1-2018, and the test temperature is 760°C.
[0062] The transverse rupture strength was tested using the method specified in the Chinese national standard GB / T 3851-2015.
[0063] The test method used for "weight gain after oxidation in 800℃ air environment for 10 hours" is: first test the weight of the mold at room temperature, then keep the mold in an 800℃ air environment for 10 hours, test its weight again after the insulation is completed, and then calculate the percentage of weight gain before and after insulation, which is the weight gain after oxidation in 800℃ air environment for 10 hours.
[0064] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing tungsten carbide-based nanocrystalline cemented carbide, characterized in that: The following steps are involved: The tungsten carbide powder is immersed in a modified solution containing a soluble cobalt salt and a soluble lanthanide metal salt, and after the immersion is completed, a solid is collected, washed and dried to obtain a first powder; calcining the first powder under a reducing atmosphere to obtain a second powder; The second powder, high entropy metal carbide powder or high entropy metal carbonitride powder and boron carbide powder are mixed, and then molded and sintered to obtain tungsten carbide-based nanocrystalline cemented carbide.
2. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 1, characterized in that: The method also includes soaking the tungsten carbide with a hydrofluoric acid solution before impregnation, and collecting, washing and drying the tungsten carbide after the soaking is completed.
3. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 2, characterized in that: The mass fraction of the hydrofluoric acid solution is 10-15%, the soaking solid-liquid ratio is 1g:(20-50mL), the soaking time is 0.5-1 hour, the soaking temperature is 40-50°C, washing to neutrality, and vacuum drying at 60-70°C.
4. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 1, characterized in that: The lanthanide metal in the soluble lanthanide metal salt is at least one of lanthanum, cerium, praseodymium, dysprosium, neodymium, promethium, samarium, europium and terbium; in the modified solution, the concentration of cobalt ions is 0.1-0.5 mol / L, and the concentration of lanthanide metal ions is 0.01-0.05 mol / L; equal volume immersion is adopted, the immersion time is 2-4 hours, the immersion temperature is 50-60°C, washing is carried out until neutral, and vacuum drying is carried out at 60-70°C.
5. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 4, characterized in that: The soluble cobalt salt is cobalt nitrate; the soluble lanthanide metal salt at least includes dysprosium nitrate, and the molar fraction of dysprosium nitrate is 40-60% of the total molar amount of the soluble lanthanide metal salt.
6. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 1, characterized in that: The reducing atmosphere is a mixture of nitrogen and hydrogen, the volume fraction of hydrogen is 20-30% of the total volume of the reducing atmosphere, the calcination temperature is 700-900° C., and the calcination time is 4-8 hours.
7. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 1, characterized in that: The weight ratio of the second powder, high entropy metal carbide powder or high entropy metal carbonitride powder, and boron carbide powder is 100:(0.2-1.5):(0.1-0.5); the metal placeholders in the high entropy metal carbide powder or high entropy metal carbonitride powder are composed of at least five of vanadium, chromium, titanium, zirconium, hafnium, niobium, tantalum, and molybdenum in an equiatomic ratio; the average particle size of tungsten carbide powder, high entropy metal carbide powder or high entropy metal carbonitride powder, and boron carbide powder is 50-150nm.
8. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 1, characterized in that: The sintering temperature is 1500-1650°C.
9. The method for preparing tungsten carbide-based nanocrystalline cemented carbide according to claim 8, characterized in that: First, sintering is performed under vacuum for 4 to 6 hours, and then sintering is performed under 100 to 200 MPa for 1 to 2 hours.
10. Tungsten carbide-based nanocrystalline cemented carbide, characterized in that: The tungsten carbide-based nanocrystalline cemented carbide is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
An ultrafine-grained cemented carbide and its preparation method
CN111378886B
Ultrafine-grained cemented carbide and preparation method thereof
CN117684036B
Process of making superfine crystal hard alloy without adhesive
CN101020971A
Method for manufacturing hard alloy
CN103789565A
Preparation method of WC-Co hard alloy with in-situ addition of rare earth oxide crystal grain refiner
CN104831098A